Website-Based Rice Harvest Data Collection Information System - Dial Dwitama Azza; Krisna Oktavian Wicaksono; David Adi Chandra (International Journal of Research and Applied Technology (INJURATECH), 2023)
The purpose of this research is to help agricultural institutions get accurate crop statistics and make it easier for farmers to submit crop data. That way farmers do not need to come directly to send their harvest data. The method used in this research is the descriptive method, by reading from various available journals. The results of this study are expected to increase the effectiveness in the delivery of crop data. With this website, the delivery of harvest data from farmers to agricultural institutions will run quickly to shorten the time. In addition, it is hoped that this website can produce precise and accurate data, to be able to answer the availability of rice and indications of a decrease or increase in the number of harvests.